The influence of abdominal adiposity and physical fitness on obesity status of portuguese adolescents - Encarnação, Samuel (2022)
The aim of this study was to verify the relationship between abdominal adiposity and physical fitness in the obesity status of Portuguese adolescents. BMI, abdominal adiposity, and physical fitness tests from the FITescola® were evaluated in a total of 654 Portuguese adolescents, aged 10-19 years old—male: n = 334 (51%), female: n = 320 (49%). For the final model, BMI was positively related with age (β = 0.25), abdominal adiposity (β = 0.313), horizontal jump (β = −0.100), 40 m maximal velocity (β = 0.274), and aerobic fitness (β = −0.250, R2 = 0.75, F = 382.2, and p = 0.0001). We conclude that higher age and abdominal adiposity are positively related with a higher adolescent BMI. Furthermore, lower horizontal jump distances and worse times on the 40 m maximal velocity were inversely related with a higher adolescent BMI, and lower aerobic fitness was inversely related with a higher adolescent BMI.